2013
DOI: 10.1103/physreve.87.051201
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of rogue waves in a variable medium: An experimental study on the interaction of water waves and currents

Abstract: We show experimentally that a stable wave propagating into a region characterized by an opposite current may become modulationally unstable. Experiments have been performed in two independent wave tank facilities; both of them are equipped with a wavemaker and a pump for generating a current propagating in the opposite direction with respect to the waves. The experimental results support a recent conjecture based on a current-modified nonlinear Schrödinger equation which establishes that rogue waves can be tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 29 publications
(40 reference statements)
5
38
0
Order By: Relevance
“…Our simulations confirm that initially stable waves in experiments of Toffoli et al (2013) undergo a modulationally unstable process and wave amplification in the presence of adverse current. Maximum amplification reasonably corresponds to results of experiments at the Tokyo University Tank for moderate strength of current.…”
Section: Nondissipative Stationary Wave Modulationssupporting
confidence: 75%
See 4 more Smart Citations
“…Our simulations confirm that initially stable waves in experiments of Toffoli et al (2013) undergo a modulationally unstable process and wave amplification in the presence of adverse current. Maximum amplification reasonably corresponds to results of experiments at the Tokyo University Tank for moderate strength of current.…”
Section: Nondissipative Stationary Wave Modulationssupporting
confidence: 75%
“…Both nonlinear instability and refractive focusing have been identified as mechanisms for extreme-wave generation and these processes are generally concomitant in oceans and potentially act together to create giant waves. Toffoli et al (2013) showed experimentally that an initially stable surface wave can become modulationally unstable and even produce freak or giant waves when meeting negative horizontal current. Onorato et al (2011) suggested an equation for predicting the maximum amplitude A max during the wave evolution of currents in deep water.…”
Section: V Shugan Et Al: An Analytical Model Of the Evolution Ofmentioning
confidence: 99%
See 3 more Smart Citations